NPAideS: a drug-checking study among 3-methylmethcathinone (3-MMC) users - Théo Willeman; Nathan Grundig; Christine Pochon; David Michels; Nicolas Charpentier; Hélène Eysseric-Guérin; Nathalie Fouilhé Sam-Lai; Françoise Stanke-Labesque; Bruno Revol (BMC, 2023)
Abstract Background 3-methylmethcathinone (3-MMC) has been available on the European drug market for several years, but an increase in its availability seems to have occurred around 2020, associated with reports of harm and death. We aimed to analyze the composition of the supposed 3-MMC samples purchased and its concordance with the assumed composition of the drug. Methods A prospective multicenter (n = 6) study was conducted between February 2021 and September 2021 in Auvergne-Rhone-Alpes, France. The inclusion criteria were: 3-MMC users over 18 years of age in contact with a community-based organization (CBO) called AIDES. Consumption was evaluated with an anonymized questionnaire and samples of 3-MMC powder were analyzed with a combination of qualitative (GC-MS) and quantitative methods (UPLC-MS/MS), to compare the assumed and real compositions of the products purchased. Results We studied 45 samples provided by 33 users. The study population was predominantly male (91%), with a median age of 40 years, most were university graduates and regular users of 3-MMC. Intravenous drug use was reported by 15.2% of the population. Most of the users bought their 3-MMC online via the Clear Web. Drug testing was requested by 86% of the users, highlighting the need for this type of harm reduction strategy. The purity of the 3-MMC powder samples tested ranged from 21 to 98%. Other NPS drugs, such as 4-CEC (4-chloroethcathinone), 4-MMC, and 2-fluorodeschloroketamine (2-FDCK), supplied as methoxphenidine (MXP), were also detected. Conclusion This prospective study shows that 3-MMC purity and dose vary considerably. It also describes the characteristics of 3-MMC users and their expectations of a drug-checking program. Our data suggest that drug-checking services may be useful in this population. Health associations and laboratories should work together to help increase access to such programs.